Petro-physical properties of Marcellus shale samples and their impact on CO2 adsorption: Equilibrium, kinetics, and empirical modeling study - Abdulkareem, F.A. (Elsevier B.V., 2020)
The correlation of CO2 adsorption characteristics with the associated shale samples mineralogy, at various total organic contents, are essential for CO2 sequestration, improved oil recovery, and gas storage operations. In this work, Marcellus shale samples from the U.S.A are studied for their CO2 adsorption capacities in term of equilibrium and kinetics. A series of analyses, including total organic carbon content, X-ray diffraction, Fourier Transform Infra-red Spectroscopy, Field Emission Scanning Electron Microscopy, temperature-programmed desorption, and N2/CO2 adsorption were performed. Gravimetric adsorption technique with magnetic suspension balance at 298 K and up to 20 bars is used to conduct isothermal adsorption and desorption measurements. Considerable organic contents of â 3-18 wt are observed. Clay minerals such as calcite, illite, kaolinite and smectite are identified with up to 50 wt ratio of some samples. Porosity and pore distribution analysis illustrate that the samples are mostly mesoporous with hysteresis supporting bottleneck or open ended-shaped pores. The temperature-programmed adsorption encouraged the phenomenon of chemisorption. Though, equilibrium isotherm modelling supported physical and chemical, heterogeneous, and multilayer adsorption. The kinetic investigation by double exponential model shows different rate of adsorption, which can be due to mineralogical alteration, physical properties or organic content. A new empirical model is developed to study the effect of relative pressure and porosity on the adsorption capacity using polynomial curve fitting technique. The model will help to predict the adsorption uptake at different operating pressures and porosity for future studies. The study can demonstrate insightful findings related to CO2 separation, sequestration and gas production for enhanced hydrocarbons recovery. Â© 2020 Elsevier B.V.